Study of Cardiac Arrhythmias in Acute Myocardial Infarction: A Hospital Based Study - Kidwai, Aasim (Journal of Nepalgunj Medical College, 2017)
Introduction: Coronary artery disease (CAD) remains the leading cause of death in the industrialized world. Majority of the deaths in MI are attributed to the development of arrhythmias during periods of myocardial infarction. Identification of the type of arrhythmia is of therapeutic and prognostic importance. Materials and methods: This was a prospective observational study conducted at the department of Internal Medicine, Nepalgunj Medical College teaching hospital, Nepalgunj for a period of 12 months. 61 consecutive cases of myocardial infarction were included in the study on the basis of inclusion and exclusion criteria. Results and discussion: Out of the 61 cases that were included in the study. 45 (73.8%) patients were above the age of 49. There was only 1 patient below 29 years of age. The commonest risk factor was hypertension which was present in 48 (78.7%) cases, followed by Diabetes Mellitus in 28(45.9%), smoking in 26(42.6%) and dyslipidemia in 12(19.7%) no. of subjects. Overall 41(67.2%) patients had anterior wall (anterior+anteroseptal+extensive anterior wall), 16(2.2%) had inferior wall (inferior+inferolateral) and 4(6.6%) had combined anterior and inferior wall myocardial infarction. Out of the 61 cases, arrhythmia was recorded in 55(90.2%) cases whereas in 6(9.8%) cases there was no evidence of any arrhythmia Ventricular premature complex was the commonest arrhythmia and was recorded in 48(78.7%) patients, followed by sinus tachycardia in 38(62.3%) patients. Ventricular tachycardia occurred in 11(18%) and ventricular fibrillation was recorded in 4(6.6%) cases. Complete heart block was seen in 7(11.5%) cases. Conclusion: Most cases of myocardial infarction develop cardiac arrhythmias. Further studies on a larger scale are needed to further understand the magnitude and spectrum of this problem in the Nepalese population.